Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.pone.0056829
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Human Phosphatidylethanolamine-Binding Protein 4 Enhances Rituximab-Induced Death and Chemosensitization in B-Cell Lymphoma

Abstract: Rituximab is the first line drug to treat non Hodgkin’s lymphoma (B-NHL) alone or in combination with chemotherapy. However, 30–40% of B-NHL patients are unresponsive to rituximab or resistant after therapy. Human phosphatidylethanolamine-binding protein 4 (hPEBP4) is a novel member of PEBP family and functions as an anti-apoptotic molecule. In this study, we found hPEBP4 to be expressed in up to 90% of B-cell lymphoma patients, but in only 16.7% of normal lymph nodes. Interestingly, hPEBP4 overexpression inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…It has been widely demonstrated that CAM-DR through direct cell contact and adhesion may be a major cause of tumor cell drug resistance in hematologic malignancies (23)(24)(25). The present study showed that adhesion to HS-5 cells or FN decreased CKIP-1 expression, and the depressed levels of CKIP-1 significantly promote the proliferation of NHL cells (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…It has been widely demonstrated that CAM-DR through direct cell contact and adhesion may be a major cause of tumor cell drug resistance in hematologic malignancies (23)(24)(25). The present study showed that adhesion to HS-5 cells or FN decreased CKIP-1 expression, and the depressed levels of CKIP-1 significantly promote the proliferation of NHL cells (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Second, transfection of interference RNA for PEBP4 into cancer cells inhibits cell proliferation, migration and invasion or induces apoptosis, whereas overexpression of this protein causes opposite changes (17, 19, 2326). Third, the expression levels of PEBP4 correlates with the sensitivity of cancer cells to chemotherapy or radiotherapy in which the upregulation of PEBP4 confers resistance to these therapies while its downregulation enhances the sensitivity (15, 26, 31, 32). These properties of PEBP4 are consistent with a role in promoting tumor transformation and progression, but are inconsistent with the inhibitory effect on the activation of the Raf-1/MEK/ERK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to PEBP1, PEBP4 was reported to associate with Raf-1 and MEK1, blocking MEK/ERK activation by TNFα or TRAIL and thereby inhibiting apoptosis (5, 15). PEBP4 is highly expressed in muscle, which leads to speculation of functional interactions between PEBP4 and Raff/MEK during myoblast differentiation (16).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the prognosis of B-NHL patients has improved significantly due to better treatments, including the application of radiotherapy, chemotherapy and immunotherapy; however, factors such as tumor cell metastasis, drug resistance and relapse affect the prognosis of patients with B-NHL (22). It has been that several factors, such as miRNA (23), CHFR prophase checkpoint gene (24) and human phosphatidylethanolaminebinding protein 4 (25), may be associated with B-NHL occurrence and development, the molecular mechanisms of which require further study. Previous studies have reported that altered miRNA expression is associated with the development of lymphoma (26,27).…”
Section: Discussionmentioning
confidence: 99%